I need some help to understand the proof of the following theorem:

Theorem If $A\subset X$ is a retract of $X$ then, $$H_n(X)\simeq H_n(A)\oplus H_n(X, A),$$ all $n\geq 0$.

Proof. Let $r:X\longrightarrow A$ be a retraction. Since $r\circ \imath=id_A$ it follows $r_*\circ \imath_*=id_{H_n(A)}$ hence $\imath_*$ is injective. Consider the exact homology sequence of the pair $(X, A)$: $$\ldots\longrightarrow H_n(A)\stackrel{\imath_*}{\longrightarrow} H_n(X)\stackrel{\jmath_*}{\longrightarrow} H_n(X, A)\stackrel{\partial}{\longrightarrow}H_{n-1}(A)\longrightarrow\ldots$$ Since $\imath_*$ is injective we find $\textrm{ker}(\imath_*)=0=\textrm{im}(\partial)$. But this says $\jmath_*:H_n(X)\longrightarrow H_n(X, A)$ is onto for all $n\geq 0$. In other words, for all $n\geq 0$, we have a short exact sequence $$0\longrightarrow H_n(A)\stackrel{\imath_*}{\longrightarrow} H_n(X)\stackrel{\jmath_*}{\longrightarrow}H_n(X, A)\longrightarrow 0,$$ which splits. Therefore, for all $n\geq 0$, $H_n(X)\simeq H_n(A)\oplus H_n(X, A)$.

Question: Where did the $0's$ in $0\longrightarrow H_n(A)\stackrel{\imath_*}{\longrightarrow} H_n(X)\stackrel{\jmath_*}{\longrightarrow}H_n(X, A)\longrightarrow 0$ come from?


We have ${\rm im}(\partial)=0$, so $\partial=0$ as map $H_n(X,A)\to H_{n-1}(A)$, so it factors through the zero object: $H_n(X,A)\to 0\to H_{n-1}(A)$. Extending the long exact sequence with these $0$'s will keep the exactness.

Anyway, injectivity of a map $f$ is equivalent to $\ker f=0$, i.e. $0\to A \overset{f}\to B$ is exact, and dually, surjectivity is equivalent to $A\to B\to 0$ being exact.

  • $\begingroup$ Your second observation was the key. I was trying to deduce the short exact sequence from the long one but what happens is that I'm considering a new sequence $0\longrightarrow H_n(A)\stackrel{\imath_*}{\longrightarrow} H_n(X)\stackrel{\jmath_*}{\longrightarrow}H_n(X, A)\longrightarrow 0$ which is exact because $\imath_*$ is injective and $\jmath_*$ is surjective.. $\endgroup$ – PtF May 4 '14 at 1:03

The reason why one can obtain a short exact sequence $0 \to H_n(A) \xrightarrow{i_*} H_n(X) \xrightarrow{j_*} H_n(X, A) \to 0$ in the proof is expressed generally by the result below

Result: Consider an exact sequence of abelian groups $$\dots \to C_{n+1} \to A_n \xrightarrow{i_n} B_n \xrightarrow{p_n} C_n \to A_{n-1} \xrightarrow{i_{n-1}} B_{n-1} \xrightarrow{p_{n-1}} C_{n-1} \to \dots$$ in which every third map $i_n$ is injective. Then the sequence $$0 \to A_n \xrightarrow{i_n} B_n \xrightarrow{p_n} C_n \to 0$$ is exact for all $n$

Now in the proof supplied in the question, we have the following long exact sequence (of abelian groups)

$$\dots H_{n+1}(X, A) \xrightarrow{\partial} H_n(A) \xrightarrow{i_*} H_n(X) \xrightarrow{j_*} H_n(X, A) \xrightarrow{\partial} H_{n-1}(A) \xrightarrow{i_*} H_{n-1}(X) \xrightarrow{j_*} H_{n-1}(X, A) \to\dots$$

and every third map $i_*$ is injective, so by the result above we obtain a short exact sequence $0 \to H_n(A) \xrightarrow{i_*} H_n(X) \xrightarrow{j_*} H_n(X, A) \to 0$ as desired.

This result quoted above is Exercise 5.14 (i) in Introduction to Algebriac Topology by J. Rotman. It is not too difficult to prove this result.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.